Application of CZE Method in Routine Analysis for Determination of B-Complex Vitamins in Pharmaceutical and Veterinary Preparations - Marina Franco; Renata Jasionowska; Elisa Salvatore (International Journal of Analytical Chemistry)
A competitive CZE method for quality control analysis of multivitamin preparations and veterinary products containing B-group vitamins was developed. Vitamins of interest are thiamine hydrochloride (B1), thiamine monophosphate chloride (B1a), riboflavine (B2), riboflavine-5′monophosphate (B2a), nicotinamide (B3), d-pantothenic acid calcium salt (B5), pyridoxine hydrochloride (B6), folic acid (B9), and 4-aminobenzoic acid (B10). These analytes were separated optimizing the experimental conditions in 20 mM tetraborate buffer pH=9.2 as a BGE (background electrolyte), on a Beckman P/ACE System MDQ instrument, using uncoated fused silica capillary. The effective capillary length was of 49.5 cm, I.D.=50 μm, the applied voltage 20 kV and the temperature 25∘C. Detection was performed by a diode array detector at 214 nm for all vitamins except B5 (190 nm) and B2a (260 nm). Separation time was about 9 min. After experimental conditions optimization, the proposed method was validated. Precision of migration time and corrected peak area, linearity range, LOD and LOQ, accuracy (recovery), robustness, and ruggedness were evaluated for each analyte demonstrating the good reliability of the method. Analyses of the pharmaceutical real samples were performed and confirmed the versatility of this method.